CRITERIA FOR EVALUATING PASSENGER WAITING TIME AT STOPS - Rakhmonov Azimjon; Bakhriddinov Dostonbek (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
This article analyzes the criteria for assessing passenger waiting time at stops in the public transport system of cities. Various factors — such as the timetable, vehicle delays, stop infrastructure conditions, and passenger satisfaction indicators — have been studied. Recommendations for improving assessment models and enhancing the quality of service are developed.